2020
DOI: 10.1371/journal.pone.0229767
|View full text |Cite
|
Sign up to set email alerts
|

Multi-well capture zones in strip-shaped aquifers

Abstract: Laboratoire de technologie écologique (ECOL), Institut des sciences et technologies de l'environnement (IIE), Faculté de l'environnement naturel, architectural et construit (ENAC), Ecole polytechnique fé dé rale de Lausanne (EPFL),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
1
0
1
Order By: Relevance
“…Ad ogni buon conto sono noti nella letteratura specialistica numerosi schemi di restituzione dell'acqua sul fronte sopragradiente rispetto a quello di pompaggio (Da Costa e Bennet 1960; Javandel e Tsang 1986; Matott et al 2006;Nagheli et al 2020). Ove sussista un dimensionamento sito-specifico corretto, tali formulazioni predispongono alla messa in opera nel sottosuolo di una sorta di cella idrodinamica attiva, in grado di isolare e controllare la zona critica e di spiazzare al contempo all'esterno del fronte di cattura, salvaguardandole, nuove acque pulite in arrivo da monte idrogeologico.…”
Section: Iwmr -Integrated Water Resource Management (Un-water Sdg6 Public Dialogue Report -Wwwunwaterorg)unclassified
“…Ad ogni buon conto sono noti nella letteratura specialistica numerosi schemi di restituzione dell'acqua sul fronte sopragradiente rispetto a quello di pompaggio (Da Costa e Bennet 1960; Javandel e Tsang 1986; Matott et al 2006;Nagheli et al 2020). Ove sussista un dimensionamento sito-specifico corretto, tali formulazioni predispongono alla messa in opera nel sottosuolo di una sorta di cella idrodinamica attiva, in grado di isolare e controllare la zona critica e di spiazzare al contempo all'esterno del fronte di cattura, salvaguardandole, nuove acque pulite in arrivo da monte idrogeologico.…”
Section: Iwmr -Integrated Water Resource Management (Un-water Sdg6 Public Dialogue Report -Wwwunwaterorg)unclassified
“…Particular P&T systems are currently implemented: [13] demonstrated that pulsed pumping can achieve similar contaminant removal for a given amount of time as continuous pumping while pumping less water; [14] studied a system of pumping wells coupled to injecting wells and demonstrate that the proper configuration of wells, varying the flow rate value many times during the year and collecting corresponding groundwater responses, is equivalent to conducting a large-scale hydraulic tomography survey, with minimal additional costs. Nagheli et al [15] studied, by means of an equation-based particle swarm optimization and genetic algorithm, the optimization of pumping and injecting wells in a multilayer configuration. These innovative improvements were devised to try to overcome the limits shown by the P&T system.…”
Section: Introductionmentioning
confidence: 99%